Magnetic Resonance Imaging of Intraplaque Hemorrhage and Plaque Lipid Content With Continued Lipid-Lowering Therapy: Results of a Magnetic Resonance Imaging Substudy in AIM-HIGH. (15th November 2022) - Zhao, Xue-Qiao; Sun, Jie; Hippe, Daniel S.; Isquith, Daniel A.; Canton, Gador; Yamada, Kiyofumi; Balu, Niranjan; Crouse, John R.; Anderson, Todd J.; Huston, John; O'Brien, Kevin D.; Hatsukami, Thomas S.; et al.
Abstract : Background: Intraplaque hemorrhage (IPH) is associated with plaque progression and ischemic events, and plaque lipid content (% lipid core) predicts the residual atherosclerotic cardiovascular disease risk. This study examined the impact of IPH on lipid content change in the setting of intensive lipid-lowering therapy. Methods: In total, 214 AIM-HIGH (Atherothrombosis Intervention in Metabolic Syndrome with Low High-Density Lipoprotein/High Triglycerides: Impact on Global Health Outcomes) participants with clinically established ASCVD and low high-density lipoprotein cholesterol received cartoid MRI at baseline and 2 years to assess changes in carotid morphology and composition. Patients were randomized to extended-release niacin or placebo, and all received simvastatin with optional ezetimibe as necessary to lower low-density lipoprotein cholesterol to 40 to 80 mg/dL. Changes in lipid content and carotid morphology were tested using the Wilcoxon signed-rank test. Differences between subjects with and without IPH and between subjects assigned extended-release niacin or placebo were tested using the Wilcoxon rank-sum test. Linear regression was used to test the association of IPH and lipid content changes after adjusting for clinical risk factors. Results: Among 156 patients (61±9 years; 81% men) with complete MRI, prior statin use: <1 year, 26%; 1 to 5 years, 37%; >5 years, 37%. Triglycerides and ApoB decreased significantly, whereas high-density lipoprotein cholesterol and ApoA1 increased significantly over time. Plaque lipid content was significantly reduced (−0.5±2.4 %/year, P = 0.017) without a significant difference between the 2 treatment groups. However, the lipid content increased in plaques with IPH but regressed in plaques without IPH (1.2±2.5 %/year versus −1.0±2.2, P = 0.006). Additionally, IPH was associated with a decrease in lumen area (−0.4±0.9 mm2/year versus 0.3±1.4, P = 0.033). IPH remained significantly associated with increase in lipid content in multivariable analysis (54.4%, 95% CI: 26.8, 88.0, P < 0.001). Conclusions: Carotid plaques under continued intensive lipid-lowering therapy moved toward stabilization. However, plaques with IPH showed greater increases in lipid content and greater decreases in lumen area than plaques without IPH. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT01178320.